Breastfeeding and factors associated with the neuropsychomotor development of children living in social vulnerability - Lara dos Santos Camilo; Nassib Bezerra Bueno; Mateus de Lima Macena; Luiz Gonzaga Ribeiro Silva-Neto; Revilane Parente de Alencar Britto; Maria Edislândia Nunes da Silva; Telma Maria de Menezes Toledo Florêncio (Instituto Materno Infantil de Pernambuco, 2024)
Abstract Objective: to determine the association between breastfeeding and associated factors with neuropsychomotor development of children living in social vulnerability. Methods: cross-sectional study within a socially vulnerable community. Households with children aged seven to 72 months, and their biological mothers were included. Sociodemographic, anthropometric and breastfeeding variables were collected using questionnaires, and neuropsychomotor development was assessed using the Denver II screening test. Adjusted prevalence ratios were calculated using multivariable models, oriented by directed acyclic graphs. Results: from the 654 households visited, 224 mother-child binomials were included. The mean age of children was 28 (18.7) months, and 143 (63.8%) of them presented suspected delay in neuropsychomotor development. Mothers presented a median of 8 years of formal schooling and 64 (28.6%) had performed exclusive breastfeeding for 6 months. Exclusive breastfeeding was not associated with neuropsychomotor development (PR=0.92; CI95%=0.84-1.00). A significant association was observed only with years of formal maternal education (PR=0.98; CI95%=0.97-0.99). A mediation analysis did not show any clear mediator between maternal education and neuropsychomotor development. Conclusions: children living in social vulnerability presented a high prevalence of suspected delay in neuropsychomotor development. Maternal education was the only variable associated with such condition.